Data collection with prioritization for wireless sensor networks - Ong, Arlyn Verina L. (Animo Repository, 2013)
Wireless sensor networks (WSN) are a popular platform to support applications that require data collection from multiple sources. Using wireless networks to provide the communication infrastructure for these sensors makes the data from sensors prone to delays and loss due to the shared nature of a wireless medium. In applications where heterogeneous sensors are crucial for data collection, sensors generate data with different levels of importance and delivery requirements. This study presents a data collection method for WSNs that provides a classification scheme for sensors, and a prioritization method used to complement a TDMA-based medium access control algorithm to arbitrate data transmission among these sensors.